Persepsi Pegawai Unit Kearsipan SKPD terhadap Aplikasi Sistem Informasi Kearsipan Daerah (SIKEDA) dan Jaringan Informasi Kearsipan Daerah (JIKEDA) di Pemerintahan Kota Bukittinggi - Suherman, Agus; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractIn this paper we discuss the SKPD Filing Unit Employee Perception of the Regional Archival Information System Application (SIKEDA) and the Regional Archival Information Network (JIKEDA) inÂ the City Government of Bukittinggi. The purpose of this study is to determine the competence and optimal shield of SKPD employees in inputting files to the SIKEDA application.This type of research is descriptive research with a qualitative approach. The location of this study was carried out in 5 SKPD Institutions in Bukittinggi, namely: (1) the Library and Archives Office of Bukittinggi City, (2) the Education and Culture Office of the City of Bukittinggi, (3) the Youth and Sports Pariwasata Service of the City of Bukittinggi, (4) the Health Service City of Bukittinggi, (5) Social Service of the city of Bukittinggi. The object of the study was SKPD employees in five government agencies in the city of Bukittinggi.Â Writing this paper aims to describe (1) To describe the optimization of the use of SIKEDA and JIKEDA applications by Admin node SIKEDA in supporting records management in the city administration of the City of Bukittinggi; (2) To describe the competencies possessed by HR in SKPD in utilizing information technology in the application of SIKEDA and JIKEDA applications in the City Government of Bukittinggi.Data was collected by observation and direct interviews with SKPD employees in the Bukittinggi city government and literature studies in the application of electronic records in the government of the City of Bukittinggi.Based on the discussion, it can be concluded that the First Employee in the SKPD in the City Government of Bukittinggi is still not optimal in inputting the archive to the sikeda Second application.iKeywords: optimization, competence, electronic archives.